STRATEGI DAKWAH MOHAMMAD NATSIR: RESPON TERHADAP KRISTENISASI DAN NATIVISASI DI INDONESIA - Rahmah, Nova Nur (JURNAL AL-AQIDAH, 2020)
The evangelism and nativisation which is one of lack of aqidah which until today remains a da’wah challenge. Muhammad Natsir as one of the leading national and international has da’wah strategy to oversee the Muslim faith. This research focuses on the study of how the Mohammad Natsir’s da’wah strategy in response evangelism and nativisation.  This is a qualitative research with a historical approach analysis, and using techniques of data collection is the library research and interviews with DDII competent administrators as a primary source. As for other sources used are books, journals that discussed the history of evangelism and nativisation in Indonesia. The analysis method used in this study is an inductive. The type of this research is explanatory. The results of this study, concluded that M. Natsir’s da’wah strategy in response to evangelism and nativisation is to strengthen the Islamic faith in a way to make people aware their existence as a Muslim and aware their missionary challenge through education, da’wah fardhiyah, structural da’wah,and cultural da’wah. The steps are chosen is to educate every Muslim and to unite ummah in the middle of Indonesian diversity. Keywords: Da’wah, Strategy, Evangelism, Nativisation.